Acacia and eucalypt plantation biosecurity in Southeast Asia – a history, and directions for future research and engagement. Issue 4 (2nd October 2022) - Healey, M. A.; Warman, R.; Mohammed, C.; Lawson, S. A.
ABSTRACT: There are over 7 million ha of eucalypt and acacia plantations in Southeast Asia (SE Asia), comprising both corporate and smallholder plantings. These plantations contribute significantly to national and regional economies and provide diverse ecosystem services. Increased trade, the global movement of people, and a changing climate increase the threat of invasive plantation pests in SE Asia. Here, we review the history of forest biosecurity research in SE Asia to determine what is needed now for the implementation of sustainable biosecurity management systems. Historically, substantial Australian aid funding has been directed at the development of eucalypt and acacia plantations in the region. Attention has been increasing on forest health and biosecurity research since the 1990s, driven by development of the timber plantation estate and the emergence of diseases such as Ceratocystis and insect pests such as Leptocybe invasa . The research agenda has focused on key insect pest and disease taxa and on understanding their biology, topical treatments, breeding responses and land-use planning approaches as means for control and management. We find there is a need for more systemic approaches, including surveillance and pre-emptive strategies, to strengthen timber plantation biosecurity. Greater consideration of socioeconomic and sociocultural contexts will be required to address these challenges. Developing new biosecurity capacity to better detect, and coordinate responses to, forest pest incursions can minimise the potential impacts of invasive pests.